Increased Biosynthetic Gene Dosage in a Genome-Reduced Defensive Bacterial Symbiont - Juan Lopera (American Society for Microbiology, 2017)
ABSTRACT A symbiotic lifestyle frequently results in genome reduction in bacteria; the isolation of small populations promotes genetic drift and the fixation of deletions and deleterious mutations over time. Transitions in lifestyle, including host restriction or adaptation to an intracellular habitat, are thought to precipitate a wave of sequence degradation events and consequent proliferation of pseudogenes. We describe here a verrucomicrobial symbiont of the tunicate Lissoclinum sp. that appears to be undergoing such a transition, with low coding density and many identifiable pseudogenes. However, despite the overall drive toward genome reduction, this symbiont maintains seven copies of a large polyketide synthase (PKS) pathway for the mandelalides (mnd), cytotoxic compounds that likely constitute a chemical defense for the host. There is evidence of ongoing degradation in a small number of these repeats—including variable borders, internal deletions, and single nucleotide polymorphisms (SNPs). However, the gene dosage of most of the pathway is increased at least 5-fold. Correspondingly, this single pathway accounts for 19% of the genome by length and 25.8% of the coding capacity. This increased gene dosage in the face of generalized sequence degradation and genome reduction suggests that mnd genes are under strong purifying selection and are important to the symbiotic relationship. IMPORTANCE Secondary metabolites, which are small-molecule organic compounds produced by living organisms, provide or inspire drugs for many different diseases. These natural products have evolved over millions of years to provide a survival benefit to the producing organism and often display potent biological activity with important therapeutic applications. For instance, defensive compounds in the environment may be cytotoxic to eukaryotic cells, a property exploitable for cancer treatment. Here, we describe the genome of an uncultured symbiotic bacterium that makes such a cytotoxic metabolite. This symbiont is losing genes that do not endow a selective advantage in a hospitable host environment. Secondary metabolism genes, however, are repeated multiple times in the genome, directly demonstrating their selective advantage. This finding shows the strength of selective forces in symbiotic relationships and suggests that uncultured bacteria in such relationships should be targeted for drug discovery efforts. Author Video: An author video summary of this article is available.